2011
DOI: 10.2169/internalmedicine.50.4855
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acquired Fanconi Syndrome Induced by Zoledronic Acid

Abstract: A 61-year-old woman with metastatic breast cancer was diagnosed as having acquired Fanconi syndrome. In this case, the cause of this syndrome was most likely zoledronic acid (Zometa ), which had been infused intravenously at a dose of 4 mg over 15 minutes weekly because of malignancy-associated hypercalcemia. Zoledronic acid is nephrotoxic and may induce severe tubular dysfunction, which can cause development of Fanconi syndrome. Therefore, close monitoring of proximal tubular function is recommended during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In fact, one study reported the development of renal dysfunction (increase in serum creatinine of 0.5 mg/dL) in 9.3% (23/246) of patients administered 4 mg/15 minute of phase III zoledronate testing and that the frequency of renal dysfunction depended on the administration time and dosage [4]. Yoshinami et al [5] reported recently a case of Fanconi syndrome caused by zoledronate, but they did not perform renal biopsy. To date, three reports have investigated zoledronate-induced renal dysfunction by renal biopsy in 8 patients [6][7][8]; however, these patients included 6 with diffuse tubular necrosis, 1 with collapsing focal glomerulosclerosis, and 1 with acute tubular necrosis, but none with Fanconi syndrome associated with interstitial nephritis.…”
Section: Case Reportmentioning
confidence: 99%
“…In fact, one study reported the development of renal dysfunction (increase in serum creatinine of 0.5 mg/dL) in 9.3% (23/246) of patients administered 4 mg/15 minute of phase III zoledronate testing and that the frequency of renal dysfunction depended on the administration time and dosage [4]. Yoshinami et al [5] reported recently a case of Fanconi syndrome caused by zoledronate, but they did not perform renal biopsy. To date, three reports have investigated zoledronate-induced renal dysfunction by renal biopsy in 8 patients [6][7][8]; however, these patients included 6 with diffuse tubular necrosis, 1 with collapsing focal glomerulosclerosis, and 1 with acute tubular necrosis, but none with Fanconi syndrome associated with interstitial nephritis.…”
Section: Case Reportmentioning
confidence: 99%
“…This syndrome can be divided into hereditary, idiopathic and acquired categories (17). Acquired Fanconi syndrome occurs mainly in adults, and one of its main causes is treatment with various drugs, including aristolochic acid, analgesics, contrast agents, expired tetracycline, aminoglycoside antibiotics, azathioprine, 6-mercaptopurine, streptozotocin, cisplatin, ranitidine, valproate anticonvulsants, and antiviral drugs such as cidofovir, tenofovir and adefovir esters (18)(19)(20)(21)(22)(23)(24)(25)(26). Tenofovir-induced Fanconi syndrome is often accompanied by acute renal failure (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…These patients were on zoledronic acid, and this agent was linked to Fanconi syndrome in two previously published case reports [15,16]. Another key differential etiology to consider includes the rare paraneoplastic syndrome called oncogenic osteomalacia, characterized by renal phosphate wasting and severe hypophosphatemia leading to osteomalacia.…”
Section: Case 2 Journal Of Case Reports and Studiesmentioning
confidence: 99%